Retraction Note: The frequency and pattern of antibiotic resistance among Klebsiella spp. isolated from nosocomial infection in Khorramabad hospital - Farah Haddadi; Mojgan Jazizadeh-Karimi; Mazhar Rostami Nejad3; Saied Sokhtehzari; Amir Hossein Monazami; Mohammad Reza Asad (Islamic Azad University, 2015)
Report of Health Care regretfully retracts the article "The frequency and pattern of antibiotic resistance among Klebsiella spp. isolated from nosocomial infection in Khorramabad hospital" which was published in this journal in December 19, 2014. Based on recommendations from COPE, we retracted this paper, which is a duplicate and self-plagiarism of the paper entitled "Comparison frequency and Determination antibiotic resistance pattern of Klebsiella SPP. isolated from Nosocomial infection in Khorramabad Shohadaye Ashayer hospital" published in Bulletin of Environment, Pharmacology and Life Sciences (November 2014; 3(12): 149-154).